Ex Vivo Assessment of an Ultrasound-Guided Injection Technique of the Lumbosacral Disc in the Horse - Robert, Mickaël; Manet, Hadrien; Manneveau, Guillaume; Geffroy, Olivier (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The aim of this study was to describe an ultrasound-guided injection technique of the lumbosacral disc in horses through the cranial vertebral notch of the sacrum and to evaluate both accuracy and potential complications of the technique on equine cadavers.Materials and Methods Twenty-four injections of the lumbosacral area were performed on 12 equine cadavers shortly after euthanasia under ultrasound guidance with the horse in recumbency using two different dyes (one colour for each side). The lumbosacral area was dissected in each horse and the accuracy of the technique, as well as its potential complications, was evaluated detecting the dyes and the structures that have been coloured.Results The lumbosacral area was correctly reached in only 11/24 injections. However, this technique allowed a lumbosacral peridiscal injection in 7/12 horses. The main difficulty was reaching the ventral opening of the L6-S1 intervertebral foramen that is partially hidden by the iliac wing on ultrasound. Puncture of the vertebral canal has been observed in 11/24 cases. The L6 spinal nerve roots emerging through the intervertebral foramen could potentially be damaged when inserting the needle.Clinical Significance The described ultrasound-guided technique allows peridiscal injection in the lumbosacral space in less than 60% of cases with potential sciatic nerve damage. Further investigations are warranted before using this technique in clinical practice in horses suffering from lumbosacral lesions.
Keywords: equine; lumbosacral joint; ultrasound; intervertebral disc; horses